Closed-Form Integrated Assessment and Uncertainty - Christian Traeger (Center for Economic Studies and ifo Institute (CESifo), 2015)
The paper derives the optimal carbon tax in closed-form from an integrated assessment of climate change. The formula shows how carbon, temperature, and economic dynamics quantify the optimal mitigation effort. The model's descriptive power is comparable to numeric models used in policy advising. Uncertainty surrounding climate change remains large. The closed-form expressions of welfare loss from shocks and epistemological uncertainty identify the interaction of (intertemporal) risk attitude, distributional moments, and the climatic shadow values. Welfare gains from reducing uncertainty about temperature feedbacks are much higher than the gains from better measurements of carbon flows.
Keywords: Q54; H43; E13; D81; D90; D61; 330; climate change; integrated assessment; uncertainty; learning; risk aversion; recursive utility; social cost of carbon; carbon tax